Music and Autism: ideas in counterpoint: ideias em contraponto (Orfeu, 2026)
This review aims to present the book Music and Autism: Ideas in Counterpoint (Oliveira, Horta, Parizzi & Sampaio, 2022). The work consists of nine chapters that explore autism and music from the perspectives of neuroscience, psychoanalysis, music therapy, and music education. The book is intended for anyone seeking more knowledge on how to engage with autistic individuals, especially those working in the fields of health and education. A key aspect of the work is the authors’ and editors’ commitment to providing information that enables autistic individuals to occupy a legitimate social and cultural space, being fully understood and accepted. In this regard, a collective investment—scientific, political, and sociocultural—is necessary to demystify autism and recognize autistic individuals as potential social agents. The book is an invitation for professionals from different fields to take responsibility in contributing to a better world, with consideration for autistic individuals.
Keywords: autism; music education; music therapy